2019
DOI: 10.1002/jor.24446
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritic Milieu Affects Adipose‐Derived Mesenchymal Stromal Cells

Abstract: The objective of this study was to define the effects of osteoarthritic (OA) milieu on good manufactured practice-adipose-derived mesenchymal stromal cells (GMP-ASC) that are commonly utilized in cell therapies. Two different OA milieu: OA synovial fluid (SF) and OAconditioned medium (CM) from synoviocytes were used to treat GMP-ASC both in normoxia or hypoxia. GMP-ASC were tested for cell migration, proliferation, cytokine receptors expression (CXCR1, CXCR2, CXCR3, CXCR4, CXCR7, CCR1, CCR2, CCR3, CCR5, IL6R),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Indeed, our data demonstrated and confirmed [22,45] the presence of proinflammatory molecules in osteoarthritic synovial fluid. As already reported [29][30][31], osteoarthritic synovial fluid influences the expression of molecules involved in immunomodulation. Furthermore, Sayegh et al recently demonstrated that coculture of AMSCs exposed to SF of patients affected by rheumatoid arthritis (RA), with activated monocyte or CD4 + cells, can inhibit the expression of CD40 and CD80 (monocyte's proinflammatory markers) and promote T reg expansion [46].…”
Section: Stem Cells Internationalsupporting
confidence: 58%
See 1 more Smart Citation
“…Indeed, our data demonstrated and confirmed [22,45] the presence of proinflammatory molecules in osteoarthritic synovial fluid. As already reported [29][30][31], osteoarthritic synovial fluid influences the expression of molecules involved in immunomodulation. Furthermore, Sayegh et al recently demonstrated that coculture of AMSCs exposed to SF of patients affected by rheumatoid arthritis (RA), with activated monocyte or CD4 + cells, can inhibit the expression of CD40 and CD80 (monocyte's proinflammatory markers) and promote T reg expansion [46].…”
Section: Stem Cells Internationalsupporting
confidence: 58%
“…Although it is well known that the use of stem cells contributes to better clinical outcomes in OA patients, the molecular mechanisms responsible for the clinical findings have not been clarified. Recently, it has been reported that the exposure of MSCs to the articular microenvironment, represented by the osteoarthritic synovial fluid, could modulate some of the stem cells' properties such as proliferation, migration, cytokine receptor expression, cytokine secretion, and inhibition of lymphocyte proliferation [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, most of the OA model was created by single cytokine supplementation in the ng/mL range in spite of several factors in the pg/mL range that are known to characterize OA-SF [ 20 ]. To date, only a few reports have described the ASC response after direct interaction with OA-SF, confirming their ability to inhibit T cell proliferation and promote T reg expansion, induce macrophage polarization into the M2-like phenotype and reduce monocyte differentiation into mature dendritic cells [ 21 , 22 , 23 , 24 ]. By preliminary analyses on a reduced number of cytokines, these effects were postulated to rely on specific ASC secreted factors (secretome) in the presence of OA-SF.…”
Section: Introductionmentioning
confidence: 99%
“…Forward and reverse oligonucleotides for PCR amplification of Glyceraldehyde 3-phosphate dehydrogenase (GAPDH), CD80, CD86, CD163, CD206, IL6,TNFα, CCL3/MIP1α, CXCL10/IP10, IL10, TGFβ1, and CCL18 are described in Table S1 and real time PCR was carried out as previously described [ 36 ]. All primer efficiencies were confirmed to be high (>90%) and comparable ( Table S1 ).…”
Section: Methodsmentioning
confidence: 99%